SOC test planning using virtual test access architectures. - Sehgal, A.
Recent advances in tester technology have led to automatic test equipment (ATE) that can operate at up to gigahertz speeds. However, system-on-chip (SOC) scan chains are typically run at lower frequencies, e.g., 10-50 MHz. The use of high-speed ATE channels to drive slower scan chains leads to an underutilization of resources, thereby resulting in an increase in SOC testing time. We present a new test planning technique to reduce the testing time and test cost by matching high-speed ATE channels to slower scan chains using the concept of virtual test access architectures. We also present a new test access mechanism (TAM) optimization framework based on Lagrange multipliers and analyze the impact of virtual TAMs on the overall SOC test power consumption for one of the ITC'02 benchmarks. Experimental results for TAM optimization based on Lagrange multipliers and virtual TAMs are presented for three industrial circuits from the set of ITC'02 SOC test benchmarks.
Keywords: ITC'02 SOC test benchmarks; Lagrange multipliers; SOC test planning; SOC test power consumption; Automatic test equipment; High speed ATE channels; System on chip scan chains; Test access mechanism optimization; Test cost reduction; Tester technology; Testing time reduction; Virtual test access architectures